Dose-response association of leisure time physical activity with mortality in adults with major chronic diseases - Sun, Jiahong; Wu, Han; Zhao, Min; Magnussen, Costan G.; Xi, Bo (Frontiers in Nutrition, 2022)
We aimed to evaluate the association between leisure-time physical activity (PA) and mortality risk in adults with major chronic diseases. A total of 170,579 adults with major chronic diseases aged 30–84 years from the U.S. National Health Interview Surveys (1997–2014) with linkage to the National Death Index (NDI) through December 31, 2015 were included in this study. During a median follow-up of 7.25 years, 36,914 adults with chronic diseases died from all causes, 8,767 died from cardiovascular disease (CVD), and 9,090 died from cancer. Compared with participants with no leisure-time PA, those with a low level (10–59 min/week) of total leisure-time PA had a 23% [hazard ratio (HR) 0.77, 95% confidence interval (CI) 0.73–0.82] reduced risk of all-cause mortality. Adults with higher levels of leisure time had more reduced risk of all-cause mortality, as well as CVD-specific and cancer-specific mortality. Adults with leisure-time PA ≥ 1,500 min/week had more reduced risk of CVD-specific mortality (61%) but less reduced risk of cancer-specific mortality (29%) compared with the reduced risk of all-cause mortality (43%). There was an inversely non-linear dose-response relationship between leisure-time PA and all-cause and cause-specific mortality. Reduced risk of all-cause and cancer-specific mortality between leisure-time light-to-moderate PA and vigorous-intensity PA time were largely comparable. Low and high levels of leisure-time PA showed substantial survival benefits compared with no leisure-time PA in adults with major chronic diseases. The light-to-moderate-intensity leisure-time PA is largely comparable with vigorous PA to provide survival benefits for all-cause and cancer-specific mortality.